Демографічні та духовні втрати українського населення на Холмщині в роки Другої світової війни та внаслідок операції «Вісла» - Годлевський, Сергій; Godlevskyi, S. (Волинський національний університет імені Лесі Українки, 2012)
У статті розглянуто втрати українського населення Холмщини і Підляшшя в роки Другої світової війни, післявоєнні конфлікти. Висвітлено трагічну долю Православної церкви на Холмщині та Підляшші й священнослужителів із 1940 до 1947 рр. Наведено відомості щодо кількості депортованого українського населення із терену Холмщини й Підляшшя внаслідок операції «Вісла». The article examines the losses of Ukrainian population in the Chelm and Podlasie regions during the Second World War and afterwars conflicts. It highlights the tragic fate of the Orthodox Church and its priests in the Chelm and Podlasie regions in 1940-1947. The article also provides data regarding the number of deported Ukranians from the Chelm and Podlasie regions as a result of Operation Vistula.
Demographic and Cultural Losses of Ukrainian Population in the Chelm Region During the Second World War and as a Result of Operation Vistula
Keywords: Холмщина; Підляшшя; Православна церква; україно-польське протистояння; священики; репатріація; виселення; операція «Вісла»; Chelm; Podlasie; Orthodox church; Ukrainian-Polish conflicts; priests; repatriation; resettlement; Operation Vistula